Nicaragua, Red de Protección Social (RPS) Evaluation Dataset, 2000-2002 - International Food Policy Research Institute (International Food Policy Research Institute, 2005)
The Nicaraguan Red de Protección Social (RPS), modeled after PROGRESA in Mexico, is a program designed to address both current and future poverty via cash transfers targeted to households living in poverty in rural Nicaragua. RPS comprised two phases over five years, starting in 2000. In order to assess whether the program merited expansion in the same or in an altered form, the Government of Nicaragua solicited various external evaluations of Phase I. The International Food Policy Research Institute (IFPRI) conducted the quantitative impact evaluation, using a randomized community-based design. The survey sample is a stratified random-sample at the comarca level from all 42 comarcas. The data originates from three phases of the survey, as well as the census and community surveys. The evaluation data are from an annual household panel data survey implemented in both intervention and control areas of RPS before the start of the program in 2000, and in 2001 and 2002 after the program began operations. The questionnaire was a comprehensive household questionnaire based on the 1998 Nicaraguan LSMS instrument, expanded in some areas (e.g., child health and education) to ensure that all the necessary program indicators were captured, but cut in other areas (e.g., income from labor and other sources) to minimize respondent burden and ensure collection of high-quality data in a single interview. An anthropometric module for children under age 5 was implemented in 2000 and 2002, but not in 2001. In this module, height (or length), weight, and hemoglobin were measured following standard international procedures.The community questionnaire was used to assess 1) whether the community has basic infrastructure, health, educational, postal services, and sources of credit; 2) other development programs present in the communities; and 3) economic events/shocks that have occurred.